Practices of preservation in the Goosetown neighborhood - Marshall, Lindsay (Archaeological Studies Program, University of Wisconsin-La Crosse, 2007)
Goosetown Neighborhood is one of the oldest working class neighborhoods in La Crosse, Wisconsin. Archaeological investigations into La Crosse's past have revealed a long and interesting history. During a redevelopment project in the 1980s, a Phase I investigation on the Jacobus house located at 608 North Sixth Street was conducted. By looking through the information in 47-LC-13, and comparing it against the procedures which took place in saving an 1858 Greek Revival house previously located at 422 North Eighth Street, information can be gained about the similarities and differences of architecture within the neighborhood, as well as the development of cultural resource management and historic preservation practices within the city.
Keywords: Goosetown (La Crosse, Wis.); Architecture, Domestic -- Wisconsin -- La Crosse; Historic preservation -- Wisconsin -- La Crosse